In Vitro antimicrobial and cytotoxic activity of Tamarix dioica - Khan, Saifullah; Ullah, Farman; Soomro, Farooq Rahman; Hussan, Maqbool (2010)
Nature has been a source of medicinal agents for thousands of years and large number of modern drugs have been isolated from natural sources, many based on their use in traditional medicine. Plants have a great potential for producing new drugs of great benefit to mankind. As a part of our drug discovery program, an effort to introduce new effective medicinal plants, with antibacterial, antifungal, and cytotoxic properties was made. The crude extract of Tamarix dioica leaves, as well as fractions in different solvents, were investigated against standard strains of bacteria Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Shigella Flexneri, Salmonella typhi, Bicillus subtilis, and Staphylococcus aureus, and fungi, Candida glabrata, Aspergilluls niger, Trichophyton rubrum, Candida tropicalis, Aspergillus fumigatus, respectively. We used brine shrimp (Artemia salina) for cytotoxicity, for bioassay in order to provide a better base for introducing the extracts as the new therapeutic candidates. Samples showed significant antifungal while low antibacterial activity. During cytotoxic study samples showed no cytotoxicity. It was recognized that Tamarix dioica has a potential for the development of new antifungal.